Spontaneous dissection of the superior mesenteric artery and the right hepatic artery: a case report - Buchs, Nicolas C (BioMed Central, 2010)
INTRODUCTION: Isolated spontaneous dissection of the superior mesenteric artery is a very rare condition. Endovascular stent placement has been proposed recently for selected cases, which has led to some good clinical results. CASE PRESENTATION: We report a case of spontaneous dissection of the superior mesenteric artery spreading to the origin of a right hepatic artery in a 48-year-old Chinese man. He benefited from the placement of an endovascular stent that yielded excellent results. CONCLUSION: Endovascular stent placement is a good alternative treatment for dissection of the superior mesenteric artery. We propose an algorithm for the management of this rare condition.